SEED PRIMING WITH NANOPARTICLES: A SUSTAINABLE APPROACH TO BOOST GERMINATION AND GROWTH IN MODIFIED MARIGOLD PLANTS - Yadav, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Applying seed priming before sowing improves how the seeds germinate, make the seedlings more alike, and helps them grow better. Recently, using nanoparticles by priming seeds has become a leading and sustainable method in agriculture. Special qualities of nanoparticles such as AgNPs and ZnONPs help improve seed plant life by boosting water intake, raising enzyme levels, and making more nutrients available. For this study, marigold (Tagetes spp.) seeds were soaked in different strengths of AgNPs and ZnONPs and their impact on seed germination and growth of the plants was studied. Germination success, length of the roots and shoots, growth of leaves, and the accumulation of biomass were better in seeds that were treated than those that were not treated. The best silver nanoparticles concentration was 100 ppm. The results indicate that using nanoparticles on seeds boosts how seeds metabolize and can be a stable way to improve the quality of plants like marigold. Nano priming is found to be a good option for increasing crop yields, requiring little investment and being environmentally safe, especially when conditions are tough.